Changes in the Sterol Composition of the Plasma Membrane Affect Membrane Potential, Salt Tolerance and the Activity of Multidrug Resistance Pumps in Saccharomyces cerevisiae - Kodedová, Marie; Sychrová, Hana (PloS one, 2015)
We investigated the impact of the deletions of genes from the final steps in the biosynthesis of ergosterol (ERG6, ERG2, ERG3, ERG5, ERG4) on the physiological function of the Saccharomyces cerevisiae plasma membrane by a combination of biological tests and the diS-C3(3) fluorescence assay. Most of the erg mutants were more sensitive than the wild type to salt stress or cationic drugs, their susceptibilities were proportional to the hyperpolarization of their plasma membranes. The different sterol composition of the plasma membrane played an important role in the short-term and long-term processes that accompanied the exposure of erg strains to a hyperosmotic stress (effect on cell size, pH homeostasis and survival of yeasts), as well as in the resistance of cells to antifungal drugs. The pleiotropic drug-sensitive phenotypes of erg strains were, to a large extent, a result of the reduced efficiency of the Pdr5 efflux pump, which was shown to be more sensitive to the sterol content of the plasma membrane than Snq2p. In summary, the erg4Δ and erg6Δ mutants exhibited the most compromised phenotypes. As Erg6p is not involved in the cholesterol biosynthetic pathway, it may become a target for a new generation of antifungal drugs.
Keywords: membránové potenciály; Cell Membrane; Hydrogen-Ion Concentration; ABC transportéry; Methyltransferases; tolerance k soli; Membrane Potentials; Drug Resistance, Multiple, Fungal; ATP-Binding Cassette Transporters; Antifungal Agents; Mutation; molekulární struktura; Biosynthetic Pathways; Saccharomyces cerevisiae Proteins; mutace; fluorescenční mikroskopie; Molecular Structure; biosyntetické dráhy; Ergosterol; buněčná membrána; Microscopy, Fluorescence; ergosterol; Saccharomyces cerevisiae; methyltransferasy; flukonazol; antifungální látky; koncentrace vodíkových iontů; mnohočetná fungální léková rezistence; Saccharomyces cerevisiae - proteiny; Fluconazole; Salt Tolerance